Governance System Impact on the Performance of Public Universities Utilizing the Centralized/Decentralized Framework - Thompson, Marcus (Advances in Social Sciences Research Journal, 2023)
This qualitative study sought to understand how centralized and decentralized governance systems impacted the performance of public universities through the perceptions of senior university administrators. Five research questions sought insights from the personal experiences of the nine participants from two governance systems, who currently hold a range of positions. The research questions were: 1) How does the administrative governance system impact the faculty and staff of the institution? 2) How does the administrative governance system impact the financial resources of the institution? 3) How does the administrative governance system impact the administrators through its policymaking function? 4) How does the administrative governance system impact student outcomes and satisfaction? 5) How does the administrative governance system monitor or evaluate the institution’s performance? Interviews of the nine participants shed light on boards engagement with universities, advocacy, shared governance, impact of board polices and institutional performance. The findings showed the need for boards to listen to all stakeholders, autonomy of institutions administrators, faculty and the need for boards to have members who understand the intricacies of the academy